A Review on Calixarene Fluorescent Chemosensor Agents for Various Analytes - Krisfian Tata Aneka Priyangga; Yehezkiel Steven Kurniawan; Keisuke Ohto; Jumina Jumina (Journal of Multidisciplinary Applied Natural Science, 2022)
Calixarenes are well-known supramolecular host molecules with versatile applications. Over the past decades, hundreds of selective and sensitive detections of several analytes have been reported by employing calixarenes as the chemosensor agent. The detection and quantification of metal ions and anions are crucial as heavy metal ions are harmful to living organisms, while monitoring anions is pivotal in the environmental samples. On the other hand, detecting and quantifying biomolecules and neutral molecules are critical due to their irreplaceable role in human health. In this review, we summarized the application of calixarenes as the supramolecular chemosensor agent for detecting metal ions, anions, biomolecules, and neutral molecules through fluorescent spectroscopy to give brief information on the design and development of the chemosensor field. This review updates the world with the application of calixarene derivatives as fluorescent chemosensors and challenges researchers to design and develop better chemosensor agents in the future.